Phytoplankton flora of Tanguar Haor ecosystem of Bangladesh: Chlorophyta (Journal of Biodiversity Conservation and Bioresource Management, 2020)
The qualitative and quantitative aspects of phytoplankton population belonging to the green algae (Chlorophyta) from Watch Tower and Rauar Station of Tanguar Haor, Sunamganj were studied. In the study, a total of 39 species of three Orders under the algal Division Chlorophyta was worked out. Their photomicrographs and individual densities in the pelagic community of phytoplankton over a study year of 2016 and 2017 are discussed. In Volvocales, Volvox carteri Stein, in Chlorococcales, Coelastrum microporum Nägeli and in Zygnematales, Staurastrum paradoxum Meyen represented the highest number of population in the community. Rauar Station was found to contain the lesser number of phytoplankton densities compared to Watch Tower Station.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 101-106